Status gizi balita sebelum dan saat Pandemi Covid-19 di wilayah kerja Puskesmas Baleendah Kabupaten Bandung - Nisatami Husnul; Wawa Sukmawati; Ade Yuliany Pratiwi (Nutrition Scientific Journal, 2023)
The Covid-19 pandemic has had a thoughtful impact on health. The social restrictions that were in effect during the pandemic have more or less affected health services, including nutrition services for toddlers. This study aims to see an overview of the nutritional status of toddlers before and during the Covid-19 pandemic in the working area of the Baleendah Health Center. The method uses descriptive analysis with a retrospective design. The nutritional status of toddlers was obtained from weighing data for February 2020 (before the pandemic) and February 2021 (during the pandemic), sourced from the Baleendah Health Center's (Puskesmas Baleendah) Toddler Weighing Month (BPB) report. The number of children under five measured was 5559 in 2021 and 3453 in 2020. The nutritional status of wasting, stunting, underweight and overweight decreased compared to before the pandemic. The nutritional status increase of normal nutritional status in the three indicators in the working area of the Puskesmas Baleendah.